Values in Motion: The Local Organic Food Co-ops Network in Ontario, Canada - Sumner, Jennifer (The International Journal of Sociology of Agriculture and Food, 2018)
Values-based food chains (VBFCs) are gaining recognition as people seek alternatives to the unsustainable environmental and social outcomes of the corporate food system. One example of a VBFC can be found in the Local Organic Food Co-ops (LOFC) Network, a coalition of cooperatives that specialize in locally and sustainably produced food in Ontario, Canada. In just a few years, the LOFC Network has built a values-based food chain comprised of producer co-ops, worker co-ops, consumer co-ops and multi-stakeholder co-ops. As a VBFC, it combines three complementary sets of values: local, organic and cooperative. Together, they form a tripartite values matrix that clearly differentiates the LOFC Network from conventional food chains, and models an alternative approach to food production, distribution and consumption. This article will present the findings of a pilot study of the LOFC Network and argue that this type of VBFC can contribute to a more sustainable food system.